Short-term recovery from prolonged exercise: Exploring the potential for protein ingestion to accentuate the benefits of carbohydrate supplements - Betts, J. A.; Williams, C. (Sports Medicine, 2010)
This review considers aspects of the optimal nutritional strategy for recovery from prolonged moderate to high intensity exercise. Dietary carbohydrate represents a central component of post-exercise nutrition. Therefore, carbohydrate should be ingested as early as possible in the post-exercise period and at frequent (i.e. 15- to 30-minute) intervals throughout recovery to maximize the rate of muscle glycogen resynthesis. Solid and liquid carbohydrate supplements or whole foods can achieve this aim with equal effect but should be of high glycaemic index and ingested following the feeding schedule described above at a rate of at least 1 g/kg/h in order to rapidly and sufficiently increase both blood glucose and insulin concentrations throughout recovery. Adding ?0.3 g/kg/h of protein to a carbohydrate supplement results in a synergistic increase in insulin secretion that can, in some circumstances, accelerate muscle glycogen resynthesis. Specifically, if carbohydrate has not been ingested in quantities sufficient to maximize the rate of muscle glycogen resynthesis, the inclusion of protein may at least partially compensate for the limited availability of ingested carbohydrate. Some studies have reported improved physical performance with ingestion of carbohydrate-protein mixtures, both during exercise and during recovery prior to a subsequent exercise test. While not all of the evidence supports these ergogenic benefits, there is clearly the potential for improved performance under certain conditions, e.g. if the additional protein increases the energy content of a supplement and/or the carbohydrate fraction is ingested at below the recommended rate. The underlying mechanism for such effects may be partly due to increased muscle glycogen resynthesis during recovery, although there is varied support for other factors such as an increased central drive to exercise, a blunting of exercise-induced muscle damage, altered metabolism during exercise subsequent to recovery, or a combination of these mechanisms.